Theoretical studies of the specialized system of automated control and management of electrically heated floor - Романченко, Микола Анастасійович; Слесаренко, Анатолій Павлович (Eastern-European Journal of Enterprise Technologies, 2013)
The results of the study of the system of automated control and management of the operating mode of specialized electric heaters of the tubular type, which are the part of the power heat-generating modules of electrically heated floor in technologically active areas of livestock production facilities of various functional purposes, are presented. The automated control system for the multilayer electric-heat-accumulating heating system of production livestock facilities was studied, which operates under the “bottom-up” scheme and allows more accurate and energy efficient observance of the set temperature mode of the electrically heated floor surface, significant reduction of the expenditure of energy carriers and fodder resources in the processes of livestock production, reduction of the negative impact of livestock production waste on the environment and improvement of production standards in the industry. The proposed automated electrotechnical complex for the use in the systems of agricultural production livestock facilities with electrically heated floors allows more efficient use of energy, fodder and investment resources in the manufacture of high-quality competitive livestock products, improvement of production standards in the industry and reduction of the negative impact of production waste on the environment. The proposed automated system of MEHHS in comparison with existing heating systems of AIC facilities allows efficient operation under the “centerperiphery” scheme in technologically safe and sustainable mode that in turn allows real-time remote control of thermal parameters of microclimate of the n-number of PLF in the large area from the single center using modern communication means